Non-noble bimetallic NiMoO4 nanosheets integrated Si photoanodes for highly efficient and stable solar water splitting. (April 2017) - Wu, Fangli; Liao, Qingliang; Cao, Fengren; Li, Liang; Zhang, Yue
Abstract: Photoelectrochemical (PEC) water splitting based on silicon (Si) is very promising because of its broad visible light absorption, earth abundance, and high carrier mobility. However, the commercial application is hindered by the poor stability and sluggish oxygen evolution reaction (OER) dynamics in electrolytes. Thanks to the non-noble bimetallic NiMoO4 nanosheet and atomic layer deposited TiO2 ultrathin film, we report a highly efficient and stable photoanode made of three-dimensional NiMoO4 nanosheet/TiO2 film/Si nanowire arrays. The NiMoO4 /TiO2 /Si composite PEC cell delivered a photocurrent density as high as 8.7 mA/cm 2 under 1 Sun illumination, which is 27 times higher than that of pristine TiO2 coated Si nanowires. Its onset potential was shifted toward the negative potential of 90 mV. The improved performance resulted from the synergistic effects of the favourable light trapping ability and the superior interface charge transfer related to the robust OER activity of NiMoO4 nanosheets. Graphical abstract: Non-noble bimetallic NiMoO4 nanosheet/TiO2 film/Si core-shell nanowire arrays were designed and synthesized by a combined process of hydrothermal, chemical etching, and atomic layer deposition. As photoanodes of photoelectrochemical cells, the hierarchical structure not only lowered the onset potential and enhanced photocurrent density, but also improved the long-term operation stability. Highlights: Non-precious bimetallic NiMoO4 nanosheets were integrated with n -type Si nanowires. NiMoO4 /TiO2 /Si nanowire composites delivered 27 times higher photocurrent than TiO2 /Si nanowires. NiMoO4 nanosheet catalysts shifted the onset potential toward the negative value of 90 mV. The composite photoanodes demonstrated excellent stability in the alkaline electrolyte.